Opinions and knowledge of the nursing students about the code of ethics for nurses and midwives - Nawalana, Anna; Majda, Anna; Mazur, Łucja (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. The code of professional conduct plays an extremely important role in the profession of nurse. Ethical rules it specifies help to develop moral sensitivity, solve ethical dilemmas and make choices. Aim. The aim of the work was to learn about the opinions and level of knowledge on the code of professional conduct among nursing students of second-cycle studies. Material and methods. The methods applied in the research included a diagnostic survey and achievement tests, with the use of an original survey questionnaire and a test of developed knowledge. The examined group included 100 nursing students of second-cycle studies at the Faculty of Health Sciences of the Jagiellonian University CM in Cracow. The acquired results were analyzed statistically. Results. The nursing students exhibited insufficient knowledge on the code of professional conduct of a nurse and midwife. Nearly 75% respondents did not know who made it. Almost all the respondents (90%) said that the code helped nurses at everyday work. Conclusions. Nurses should broaden and supplement their knowledge on the code of professional conduct. Acting according to ethical rules helps to work with patients and with the remaining medical team members.